Periodontal Regeneration Using Platelet-Derived Growth Factor in Infrabony Defects: A Series of Three Cases - Kaustubh Thakare; M. L. Bhongade; Preeti Charde; Priyanka Jaiswal; Nachiket Shah; Aniruddha Deshpande (Case Reports in Dentistry)
The periodontal researchers and clinicians, in an effort to develop effective regenerative therapies, have sought to understand key events involved in the regeneration of periodontium. Polypeptide growth factors are a class of natural biological mediators which regulate key cellular events in tissue repair. Platelet-derived growth factor (PDGF) is the most thoroughly studied growth factor in periodontal regeneration. The present case series evaluate the effectiveness of platelet-derived growth factor (rh-PDGF-BB) in combination with beta-tricalcium phosphate (β-TCP) to achieve periodontal regeneration in 3 infrabony defects.